Moving Beyond Text: How Teens Evaluate Video-Based High Stakes Health Information via Social Media - Booth, Kayla M.; Trauth, Eileen M. (Information in Contemporary Society, 2019)
This paper qualitatively examines how teenagers in the US evaluate high stakes health information via social media. Through 30 semi-structured interviews with teens ages 13–18, we explore how teens interact with and make decisions about the quality of video-based exercise and nutrition content. Participants indicated that they are wary of advertisements and language that encourages extreme weight loss, yet prefer video content that is “fun” and engaging. Additionally, participants reported having explicit and implicit criteria for evaluating videos with health content that includes both graphic and content quality.